2021
DOI: 10.3390/molecules26103053
|View full text |Cite
|
Sign up to set email alerts
|

TAK1/AP-1-Targeted Anti-Inflammatory Effects of Barringtonia augusta Methanol Extract

Abstract: Barringtonia augusta methanol extract (Ba-ME) is a folk medicine found in the wetlands of Thailand that acts through an anti-inflammatory mechanism that is not understood fully. Here, we examine how the methanol extract of Barringtonia augusta (B. augusta) can suppress the activator protein 1 (AP-1) signaling pathway and study the activities of Ba-ME in the lipopolysaccharide (LPS)-treated RAW264.7 macrophage cell line and an LPS-induced peritonitis mouse model. Non-toxic concentrations of Ba-ME downregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…It has been reported that the MAPK families include extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), and p38 kinase. Therefore, targeting the MAPK pathway is a significant and attractive therapeutic anti-inflammatory method [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the MAPK families include extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), and p38 kinase. Therefore, targeting the MAPK pathway is a significant and attractive therapeutic anti-inflammatory method [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these results might suggest that p38 of MAPK might be an upstream target of Pd-EE contributing to its AP-1 pathway inhibitory activity. Considering that Saururus chinensis and Barringtonia augusta inhibited TAK1, an upstream enzyme to activate MAPK and AP-1, and Cerbera manghas reduced the enzyme activity of JNK, one of MAPKs [ 50 , 51 , 52 ], Pd-EE might block one of the upstream enzymes to activate AP-1 pathway. In addition, it is expected that Pd-EE can inhibit one of the upstream kinases regulating NF-κB pathway, since Src, Syk, PDK1, AKT, and IKK were targeted by several NF-κB-inhibitory plants including Olea europaea , Mycetia cauliflora , Lilium brownii , and Chrysanthemum indicum [ 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…TAK1 also increases phosphorylation of mitogen-activated protein kinase (MAPK), including p38, extracellular signal-regulated kinase (ERK), and c-Jun N-terminal kinase (JNK), resulting in the continuous phosphorylation of AP-1 subunits, e.g., c-Jun and c-Fos [ 19 , 20 , 21 , 22 , 23 ]. Both NF-κB and AP-1 translocate into the nucleus after their phosphorylation, acting as a pivotal transcription factor for inflammatory responses [ 24 , 25 ]. Immune cells utilize these processes to secrete pro-inflammatory cytokines that trigger neutrophil infiltration and activation of lymphocytes for further immunological activation [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%